A single centre experience in the management of undescended testes - Ramesh Singh L; Khuraijam Gojen Singh; Nongmaithem Mackson Singh; Sunilkumar Singh Salam; Laitonjam Chinglensana; Irom keshorjit singh keshorjit singh (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Undescended testes (UDT) is one of the most common congenital anomalies of the urogenital system. In spite of its common occurrence, lots of variations are still reported regarding the time of surgery, mode of investigation and surgery. The present study tried to report the single centre experience of management of UDT.Materials and Methods: The data of patients with UDT including time of presentation, time of surgery, position of testes, investigations, associated urogenital anomalies, complications were collected over a period of 9 years and 6 months and analysed.Results: A total of 118 children were recorded of which the testes of 6 infants became descended before the age of 6 months. Out of the remaining, 112 children, 24 children had bilateral UDT, 24 children had nonpalpable testes (NPT). Ultrasound could locate 19 NPT pre-operatively. Maximum children were operated between 6 months to 1 year in 43 children (38.39 %). Laparoscopy was done for intra-abdominal testes and NPT whose locations could not be located by US and the rest by open inguinal exploration. Four children had pre-operative complications with obstructed inguinal hernias (2 cases) and testicular torsion (2 cases).Conclusion: Majority of the children were being operated before the age of 1 year and US is a good non-invasive to effectively locate the NPT.